Comparison of the model for end-stage liver disease and disease sodium values in prognosticating short term 3-month mortality in chronic liver disease - Nandalike, Prathvi; Fathima, Nimrah; Reddy, Machandra; B., Sandhya Rani; P., Srinivas (International Journal of Research in Medical Sciences, 2022)
Background: Chronic liver disease (CLD) cirrhosis of liver is one of the common non communicable disease, accounting for significant morbidity and mortality in developing countries like India. several prognostic scoring systems have evolved from the need to prioritize patients for liver transplantation model for end-stage liver disease (MELD) and its variant, which includes sodium values (MELD-Na) have been recently popularized. Methods: Prospective observational study with follow-up telephone call every month for 3 months, with ppurposive sampling done on 60 patients admitted to AIMS BG Nagara Mandya district Karnataka India. Statistical analysis included the strength of association was assessed using Pearson’s correlation and the ROC curve was drawn to assess the accuracy and diagnostic utility of the two models. A p<0.05 was considered statistically significant. Results: In the present study, the mean age of patients was 49.68±9.89 years of age. The strength of association between the MELD score and MELD-Na score was found to be a very strong positive strength of association (r=0.904, p<0.05). The mean MELD score and MELD-Na score was found to be higher in non-survivors’ group (28.5 and 30.5) compared to survivors group (22.03 and 25.67) which was statistically very significant. Conclusions: MELD-Na score was higher among the patients with outcome of death compared to the MELD score among the patient. The ROC curve showed a comparable result with MELD and MELD-Na scores. There was a relation of severity of hyponatremia with the child-Pugh scores.